Therapeutic challenges and mortality outcomes in HFrEF patients with CKD:a multi-centre and multi-ethnic experience - A.Z. Y., Koh; B. K., Chung; Hwei Sung, Ling; C. Z. F., Chua; W. K., Ho; K. C., Cheah; S. L., Kwa; J., Namasoo; C. H., ChaI; P. W., Ting; M. J., Khaw; J. K. W., Wong; et al. (European Society of Cardiology, 2025)
Introduction: The presence of chronic kidney disease (CKD) in patients with heart failure (HF) is associated with increased complications, readmissions, and mortality. CKD can also limit the application of guideline-directed medical therapy (GDMT) for HF in routine clinical practice. The comparative clinical outcomes of HF patients with CKD versus non-CKD patients in dedicated HF clinics remain uncertain. Purpose: To evaluate the characteristics and clinical outcomes of patients with chronic heart failure with reduced ejection fraction (HFrEF) and CKD compared to non-CKD patients. Methods: A retrospective, multi-center cohort study analyzed 465 patients with HFrEF who attended dedicated HF clinics in ten hospitals between January 1, 2021, and June 30, 2023. Clinical records, baseline characteristics, and six-month clinical outcomes were evaluated. CKD is defined as having an estimated glomerular filtration rate (eGFR) of less than 60 ml/min/1.73m2 according to the 2021 CKD-EPI. Results: Among the 465 patients, 129 (27.7%) had CKD and 336 (72.3%) were non-CKD. CKD patients were significantly older (61±11 years vs. 53±13 years, p=0.002), but both groups had a similar male predominance (77% vs. 77%, p=0.487). CKD patients exhibited higher rates of hypertension (79% vs. 61%, p<0.001), diabetes mellitus (50% vs. 35%, p=0.002), dyslipidemia (61% vs. 49%, p=0.014), cerebrovascular accidents (12% vs. 6%, p=0.033), and anemia (39% vs. 22%, p<0.001). However, there were no significant differences in the prevalence of ischemic heart disease (50% vs. 44%, p=0.157) or atrial fibrillation (25% vs. 22%, p=0.292). The prescription of renin-angiotensin-aldosterone system (RAAS) inhibitors was significantly lower in the CKD group at first clinic visit (69% vs. 88%, p<0.001), three months (73% vs. 93%, p<0.001), and six months (78% vs. 92%, p<0.001). In contrast, prescriptions of beta-blockers, mineralocorticoid receptor antagonists, and sodium-glucose cotransporter-2 inhibitors were similar across groups at all time points. Both groups demonstrated significant improvement in left ventricular ejection fraction (LVEF) over six months, with no intergroup differences: 29.3±9.8% to 37.2±14.1% (CKD) vs. 26.9±7.8% to 38.3±13.0% (non-CKD, p=0.161). Similarly, there was no significant difference in improvement in NYHA functional class (p=0.795). However, the CKD group experienced higher six-month all-cause mortality (16.5% vs. 5.6%, p<0.001), while the six-month HF readmission rate was comparable (10.9% vs. 6.0%, p=0.057). Conclusion: Both CKD and non-CKD patients with HFrEF showed improvement in LVEF and NYHA functional class during follow-up in dedicated HF clinics. However, CKD patients had lower RAAS inhibitor prescriptions and significantly higher six-month all-cause mortality, emphasizing the need for optimized management strategies for this high-risk group.